STUDENTS’ PERCEPTION OF USING SCAVENGER HUNT GAME IN UNDERSTANDING SOCIAL CONTEXT OF SECOND LANGUAGE ACQUISITION - Rosyidi, Ahmad Zuhri; Muliadi, Mul; Hadi, M. Wahyu; Alawiya, Rizky (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research study investigates students’ perception of using the Scavenger Hunt game to understand the social context of second language acquisition. The participant of this research was 12 undergraduate students in the 5th semester. The data were collected from questionnaires, documentation, and interview. The data were analyzed using descriptive analysis. This study revealed that Scavenger Hunt is an exciting way to understand the social context of Second Language Acquisition because the students experienced directly and what they did were examples of some issues in learning the social context of Second Language Acquisition (SLA). Teachers and lecturers should consider the integration of Scavenger Hunt and specific topics with some adaptation to make the activity effective in the teaching and learning process.